Writing back to Brexit: refugees, transcultural intertextuality, and the colonial archive - Rupp, Jan (Journal of postcolonial writing, 2020)
This article deals with the role of transcultural intertextuality in writing refugees and Brexit, arguing that refracting the colonial archive has served contemporary accounts of refugee migration to interpret current scenarios, revise lingering colonial imaginaries, and forge new bonds of solidarity. It draws on recent work in transcultural memory studies to explore how emergent bodies of refugee writing have remembered and actualized canonical works by engaging and adding to their relational mnemohistories. A multilateral account of the transcultural travel of memories, including of literary texts, relational mnemohistory allows one to rethink the constellation of source-text and actualization in intertextuality theory. While by no means reducible to writing back to Brexit and the canon, recent literature of the Calais “Jungle” migrant camp, such as the play The Jungle (2017), as well as works like the multi-volume Refugee Tales, performs important cultural work, retrieving historical entanglements and envisioning a much-needed relationality for the present.